2018
DOI: 10.3389/fpsyg.2018.00290
|View full text |Cite
|
Sign up to set email alerts
|

Action Prediction Allows Hypothesis Testing via Internal Forward Models at 6 Months of Age

Abstract: We propose that action prediction provides a cornerstone in a learning process known as internal forward models. According to this suggestion infants’ predictions (looking to the mouth of someone moving a spoon upward) will moments later be validated or proven false (spoon was in fact directed toward a bowl), information that is directly perceived as the distance between the predicted and actual goal. Using an individual difference approach we demonstrate that action prediction correlates with the tendency to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 65 publications
8
54
0
Order By: Relevance
“…Following Gredebäck, Lindskog, et al (), this is a combined measure of infants' action prediction and action evaluation scores ( r = .41, p < .000). The measure was constructed by first reversing the action prediction variable and then averaging standardized scores from the two tasks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Gredebäck, Lindskog, et al (), this is a combined measure of infants' action prediction and action evaluation scores ( r = .41, p < .000). The measure was constructed by first reversing the action prediction variable and then averaging standardized scores from the two tasks.…”
Section: Methodsmentioning
confidence: 99%
“…The measure was constructed by first reversing the action prediction variable and then averaging standardized scores from the two tasks. The action prediction and action evaluation tasks are described briefly below (see Gredebäck, Lindskog, et al, for detailed task information). Positive values on this measure indicate that the participant was faster at predicting goal‐related actions (i.e., action prediction) and/or reacted with more surprise when events unfolded in an inappropriate way (i.e., action evaluation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work suggests that infants in previous studies using looking time measures may not have simply been responding passively to the action taken by the agent, but may instead have actively generated a prediction about her behavior and responded when that prediction was violated. However, at 6 months, the ability to generate action predictions may still be developing; Gredebäck, Lindskog, Juvrud, Green, and Marciszko () found individual differences in 6‐month‐olds’ ability to generate action predictions, and further found that this ability correlates with infants’ ability to evaluate whether actions unfold appropriately (e.g., an object placed in an agent's outstretched hand rather than on her head), suggesting an emerging competence for action understanding at 6 months. Indeed, action prediction may be supported at least in part by the motor system (Gredebäck & Falck‐Ytter, ; Krogh‐Jespersen & Woodward, ; Kanakogi & Itakura, ), which at 6 months is still developing.…”
mentioning
confidence: 99%
“…We chose to test 6‐month‐old infants, for two reasons. First, infants of this age have previously been shown to successfully infer agents’ goals from their preferential reaching behavior (Luo & Baillargeon, ; Woodward, ) and to make gaze predictions based on agents’ goals (Kim & Song, ; Kochukhova & Gredebäck, ), albeit with some variability (Gredebäck et al., ). Second, and most importantly, 6‐month‐olds’ ability to maintain representations of two occluded objects (in the absence of a social agent) is well understood (Káldy & Leslie, ; Kibbe & Leslie, , , in press).…”
mentioning
confidence: 99%